Status and Role of Goddesses as Representations of Women: A Study of East Javanese Myths - Fitrahayunitisna Fitrahayunitisna (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
his study examines the status and roles of goddesses in myths in East Java as representations of women. The aim is to explore the status and roles of goddesses as a woman which are very important and not marginalized. There has been a controversial debate over the role of Indonesian women for several decades by scholar from functionalist and feminist paradigms. This study offers a perspective from the structuralist paradigm. Using a structuralism research design, 21 myths of goddesse from East Java as the data supported by interviews, observations, and document studies. The study shows that the goddesses in myths occupy important status and roles, especially in politics and religion. This study shows that the role of goddesses as a woman in the domestic and public spheres is very significant for a civilization. The role of goddesses as a woman in the public and domestic spheres is not strictly separated but flexible. The status of goddesses as a woman in their social reality is highly respected, and their roles are also important. These findings offer an alternative framework as a contribution for reading women’s status and roles through mythic representation rather than relying only on present-day social observation.